Essentials of Oral Carcinoma: A Review - Sashikant Sethy1 , Radha Prasanna Dalai2 , Sourav Chandra Bidyasagar Bal1 , Asima Biswal3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In recent periods Oral carcinoma has become a highly significant threat to whole public health in the worldand, specifically for dentists. Oral carcinoma comes within the top ten rankings among all carcinoma in theworld. lots of research work is going on about the carcinoma, after that prognosis rate is not so impressiveto date which is going to be a great challenge to medical science. Oral squamous cell carcinoma can berepresented as “natural course”, which originated from non-aberrant keratinocytes cells, with history oflong term exposure to a various stimulus that breaks down homeostasis process of it, Leads to hyperplasia,dysplasia in terms of various degrees, carcinoma in situ with lots of clinical oral manifestations. This naturecourse offers a roadway for various research approaches in medical science. The very early recognizableclinical alteration that can any epithelium on his path to creating an Oral squamous cell carcinoma ispredominantly the generation of malignant fatal disease, like leukoplakia, lichen planus, erythroplasia aremost common.